2000
DOI: 10.1002/(sici)1521-4176(200003)51:3<155::aid-maco155>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Anodising as pretreatment of durable aluminium: The behaviour of several aluminium alloys to filiform corrosion

Abstract: Aluminium alloys AA 3005, AA 3103 and AA 6063 were anodised in sulphuric acid under different conditions whereby a set of porous layers with varying thicknesses was produced. The influence of porous layer thickness on the filiform corrosion behaviour was examined by means of the Lockheed test. The filiform corrosion behaviour as a function of time was investigated. It appeared that the alloys showed similar filiform corrosion behaviour since for all alloys filiform corrosion was reduced considerably by increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Anodizing is an oxidation process that produces a thick oxide film (micrometer scale) on the aluminum surface for multifunctional purposes (e.g., corrosion resistance, electrical insulation, or decorative applications) using a concentrated acid solution and application of an external dc current. Previous work [15][16][17] has shown that this oxide film consists of a porous closed-packed structure array with columnar hexagonal-shaped cells each containing thin pores separated from the substrate surface by a thin uniform and compact inner barrier layer (nanometer scale). In applications where the anodized aluminum is exposed to corrosive atmospheres sealing of the anodic oxide films is required because the porosity of the oxide layer decreases the corrosion resistance of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Anodizing is an oxidation process that produces a thick oxide film (micrometer scale) on the aluminum surface for multifunctional purposes (e.g., corrosion resistance, electrical insulation, or decorative applications) using a concentrated acid solution and application of an external dc current. Previous work [15][16][17] has shown that this oxide film consists of a porous closed-packed structure array with columnar hexagonal-shaped cells each containing thin pores separated from the substrate surface by a thin uniform and compact inner barrier layer (nanometer scale). In applications where the anodized aluminum is exposed to corrosive atmospheres sealing of the anodic oxide films is required because the porosity of the oxide layer decreases the corrosion resistance of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The 10-fold reduction in dA/dt compared with unpigmented PVB in the absence of an ES-induced oxide film suggests that the oxide layer disfavours underfilm anodic attack. It has been demonstrated elsewhere [40,41] that anodization of a range of aluminium alloy substrates strongly suppresses FFC, and that both the number of filaments and propagation rate become progressively reduced as the anodic oxide thickness is increased. Given the arguments presented previously regarding the relative contribution of substrate ennoblement and ion exchange, it therefore seems plausible to postulate that "self-anodization" by the ES-based coating, leading to the formation a protective interfacial oxide, is the principal mode by which PAni/pTS inhibits FFC on AA2024-T3.…”
Section: Protection By An Interfacial Oxide Layermentioning
confidence: 99%
“…El anodizado y lacado son las operaciones industriales más utilizadas, con mucho, para prevenir el ataque localizado y asegurar la permanencia de las propiedades y del aspecto. Sin embargo, en atmósferas muy agresivas, como pueden ser las marinas y las industriales, los fenómenos de corrosión localizada, esencialmente la corrosión filiforme en los elementos lacados [4][5][6][7][8][9] y por picaduras en los anodizados [10][11][12][13][14] , producen serios deterioros estéticos. La seguridad y propiedades mecánicas no sufren, en cambio, limitaciones significativas, debido a la naturaleza superficial del ataque [6] .…”
Section: Effect Of Aluminium Alloy Surface Heterogeneities On Anodic unclassified